Lower ghrelin levels does not impact the metabolic benefit induced by Roux-en-Y gastric bypass - Liang, Yuan; Yu, Ruili; He, Rui; Sun, Lijun; Luo, Chao; Feng, Lu; Chen, Hong; Yin, Yue; Zhang, Weizhen (Frontiers in Endocrinology, 2022)
Objective: Roux-en-Y gastric bypass is an effective intervention for metabolic disorder. We aim to elucidate whether ghrelin contributes to weight reduction, and glycemic and lipid control after Roux-en-Y gastric bypass (RYGB). Design: Four-week-old WT and Ghrl-TSC1-/- mice were fed high fat diet for 12 weeks before surgery, and continued to be on the same diet for 8 weeks after surgery. Body weight, food intake, glycemic and lipid metabolism were analyzed before and after surgery. Results: Gastric and circulating ghrelin was significantly increased in mice with RYGB surgery. Hypoghrelinemia induced by deletion of TSC1 to activate mTOR signaling in gastric X/A like cells demonstrated no effect on weight reduction, glycemic and lipid control induced by Roux-en-Y gastric bypass surgery. Conclusion: Ghrelin is not necessary for the metabolic benefit induced by Roux-en-Y gastric bypass.